Individual reproductive success in Norway spruce natural populations depends on growth rate, age and sensitivity to temperature - Avanzi, Camilla; Heer, Katrin; Büntgen, Ulf; Labriola, Mariaceleste; Leonardi, Stefano; Opgenoorth, Lars; Piermattei, Alma; Urbinati, Carlo; Vendramin, Giovanni Giuseppe; Piotti, Andrea (Heredity, 2020)
Quantifying the individual reproductive success and understanding its determinants is a central issue in evolutionary research for the major consequences that the transmission of genetic variation from parents to offspring has on the adaptive potential of populations. Here, we propose to distil the myriad of information embedded in tree-ring time series into a set of tree-ring-based phenotypic traits to be investigated as potential drivers of reproductive success in forest trees. By using a cross-disciplinary approach that combines parentage analysis and a thorough dendrophenotypic characterisation of putative parents, we assessed sex-specific relationships between such dendrophenotypic traits (i.e., age, growth rate and parameters describing sensitivity to climate and to extreme climatic events) and reproductive success in Norway spruce. We applied a full probability method for reconstructing parent-offspring relationships between 604 seedlings and 518 adult trees sampled within five populations from southern and central Europe. We found that individual female and male reproductive success was positively associated with tree growth rate and age. Female reproductive success was also positively influenced by the correlation between growth and the mean temperature of the previous vegetative season. Overall, our results showed that Norway spruce individuals with the highest fitness are those who are able to keep high-growth rates despite potential growth limitations caused by reproductive costs and climatic limiting conditions. Identifying such functional links between the individual ecophysiological behaviour and its evolutionary gain would increase our understanding on how natural selection shapes the genetic composition of forest tree populations over time.
Keywords: lesy; teplota; Picea; Reproduction; smrk; rozmnožování; Temperature; Europe; Forests; Evropa